A Meta-Analysis of the Effectiveness of Restorative Justice Programs in Reducing Recidivism: A Global Perspective - Syahwami, Syahwami; Hamirul, Hamirul (Enigma in Law, 2024)
Restorative justice (RJ) is a growing alternative to traditional punitive justice, emphasizing offender accountability, victim reparation, and community reintegration. This meta-analysis aims to quantify the effectiveness of RJ programs in reducing recidivism across diverse global contexts. A systematic search of electronic databases (Scopus, Web of Science, PsycINFO) from 2018-2024 was conducted, including studies that assessed the impact of RJ on recidivism using experimental or quasi-experimental designs. The primary outcome was recidivism (any reoffense), with secondary outcomes of violent and non-violent recidivism. Random effects models were used to calculate pooled effect sizes. Thirty-two studies met the inclusion criteria (N = 18,654 participants). The overall pooled effect size for RJ on recidivism was -0.11 (95% CI -0.15, -0.07), indicating a small but statistically significant reduction in recidivism compared to traditional justice. Subgroup analyses revealed greater effects for youth offenders (-0.16) and for programs with high adherence to core RJ principles (-0.18). In conclusion, RJ programs demonstrate a modest but consistent effect in reducing recidivism. The findings support the continued implementation and expansion of RJ, particularly for young offenders and in settings with strong adherence to RJ philosophy.